A drug repurposing screen for whipworms informed by comparative genomics. - Avril Coghlan; Frederick A Partridge; María Adelaida Duque-Correa; Gabriel Rinaldi; Simon Clare; Lisa Seymour; Cordelia Brandt; Tapoka T Mkandawire; Catherine McCarthy; Nancy Holroyd; Marina Nick; Anwen E Brown; et al. (PLoS Neglected Tropical Diseases)
Hundreds of millions of people worldwide are infected with the whipworm Trichuris trichiura. Novel treatments are urgently needed as current drugs, such as albendazole, have relatively low efficacy. We have investigated whether drugs approved for other human diseases could be repurposed as novel anti-whipworm drugs. In a previous comparative genomics analysis, we identified 409 drugs approved for human use that we predicted to target parasitic worm proteins. Here we tested these ex vivo by assessing motility of adult worms of Trichuris muris, the murine whipworm, an established model for human whipworm research. We identified 14 compounds with EC50 values of ≤50 μM against T. muris ex vivo, and selected nine for testing in vivo. However, the best worm burden reduction seen in mice was just 19%. The high number of ex vivo hits against T. muris shows that we were successful at predicting parasite proteins that could be targeted by approved drugs. In contrast, the low efficacy of these compounds in mice suggest challenges due to their chemical properties (e.g. lipophilicity, polarity, molecular weight) and pharmacokinetics (e.g. absorption, distribution, metabolism, and excretion) that may (i) promote absorption by the host gastrointestinal tract, thereby reducing availability to the worms embedded in the large intestine, and/or (ii) restrict drug uptake by the worms. This indicates that identifying structural analogues that have reduced absorption by the host, and increased uptake by worms, may be necessary for successful drug development against whipworms.